i-CLUB UiTM club management application using Analytic Hierarchy Process (AHP) for selecting the recommended activity based on student criteria / Ahmad Aiman Haziq Ahmad Tarmidzi, Muhammad Amirul Abdul Manan and Khairul Rashid Mat Riffin - Ahmad Tarmidzi, Ahmad Aiman Haziq; Abdul Manan, Muhammad Amirul; Mat Riffin, Khairul Rashid (2018)
Any club plays an important role in improving and supporting every aspect of the experience and disclosure required by the students. From celebrating cultural diversity to offering professional guidance and support, the club is created, run and formed by students along with the faculty. Club functions in exchange for both past experiences and new ideas, complementing the academic environment of collaboration that is per-needs of today. Clubs at UiTM Seremban 3 does not have mobile apps specifically for clubs to disseminate their activities or events to students. So we came up with ideas for developing apps to solve this problem. Our main objective is to extract recommended activities run by clubs in UiTM Seremban Campus Club based on students' interest using the Analytical Hierarchy Process (AHP) method. AHP is used to find the best activities for students according to the criteria choose. The second goal is to develop a mobile application which can be used by club admin. With this application, club management will be more organized and efficient. We provide a platform that will facilitate the club management process to distribute information of an event that is being conducted. They will also be easy to get respondent to join their event because this application provides the accurate information of every clubs in the campus where it is filled by the members of the club. This Application was developed by using Java language and implemented by using Android studio.